Legitimacy in University Government: A New Typology - Andres Bernasconi; Paula Clasing (Arizona State University, 2015)
We propose a typology of forms of legitimacy of authority in the university, based on the well-known classification by Max Weber of the forms of political authority based on the types to legitimacy typically invoked by those in a position of authority. This framework is adapted and expanded to the field of university governance taking into consideration the specialized literature on models of governance in higher education, and with the aid of data obtained from interviews of former university leaders with whom we discussed their experiences as university officials. Our typology consists of six forms of legitimacy: traditional, which distinguishes two forms, academic and administrative; rational-bureaucratic, which also has two modalities, managerial and legalistic, and finally, the political and charismatic forms. To stress the differences across these types of legitimacy, and try out a possible translation of them into designs amenable to empirical research, we also present an operationalization of the typology into variables and hypotheses.